Черный бумер: [роман] / Андрей Троицкий - Троицкий Андрей Борисович (Русский проект, 2006)
Экземпляры: ф.23 (2007) / Инвентарный номер: 50474 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Т 70 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44